L-pidolato de cálcio e redução da proteína bruta da ração para reprodutoras de codornas de corte - Corrêa, Antonia Renata Lima (2022)
The goal of the current project was to study the effects of the Calcium L-Pidolate (CaLP) inclusion and the reduction in crude protein (CP) content in the diet of two lineages of broiler quail breeding at an advanced age. There were 360 females used and 120 males, with 28 weeks of age, half of each of the fujikura lineages (L1) and UFC (L2) lineages integrated into a completely randomized design in a factorial scheme (2 lineages x 2 levels of CP x 3 levels of CaLP), totaling 12 treatments, with 5 repetitions of 8 birds, this being constituted of six females and two males. The treatments applied were: T1 – feeding without addition of CaLP and without reduction of CP (Control); T2 – ration with addition of 0.015% of CaLP and 22% CP; T3 – diet with 0.030% of CaLP and 22% CP; T4 – diet without addition of CaLP and 19,8% CP; T5 – with 0.015% of CaLP and 19,8% CP; T6 – 0.030% of CaLP and 19,8% CP. The experimental period was 126 days and observed breeder performance, egg quality, hatchery parameters and progeny performance. There was no significant interaction of the factors studied on the variables evaluated. The lineages differed only for the specific density of eggs, with a higher value for eggs from L1. The level of CP in the diet and the addition of calcium L-Pidolate significantly influenced egg production and feed conversion, with no change in consumption, egg weight and mass, egg quality, incubation parameters and progeny performance up to 21 days of age. Regardless of the lineage, the reduction of crude protein, from 22% to 19.8%, in feed for broiler quail breeders with 2800 kcal of metabolizable energy or the addition of 0.030% of LPCa contributes to increase the production of breeding quail eggs.